Where Do Banks End and NBFIs Begin? - Acharya, Viral V; Cetorelli, Nicola; Tuckman, Bruce (The Review of Corporate Finance Studies, 2026)
Abstract Nonbank financial intermediaries (NBFIs) have grown significantly relative to banks. We argue that this growth reflects a transformation of the activities and risks of banks and NBFIs, driven at least in part by changes in bank regulation. We document through new regulatory data, case studies, and empirical analyses that banks remain special as providers of both routine and emergency liquidity to NBFIs and that the sectors have become increasingly interdependent. We discuss some potential regulatory responses, including considering the two sectors holistically and exploring new ways to internalize the costs of systemic risk arising from bank-NBFI interconnectedness. (JEL: G01, G21, G23, G28)